PEMBANGUNAN SEGITIGA STRATEGI SEBAGAI MEDIA PROMOSI BERBASIS WEBSITE DENGAN FITUR DAILY DEALS DI PT XYZ - Ridhowati, Ridhowati (Bajang Institute, 2024)
Marketing strategy is one way to win sustainable competitive advantage for companies that produce goods or services. So you need the right strategy in the marketing process, both directly and online, to get the right results. The results of this research to obtain the right marketing strategy are (1) Maintaining or improving company performance to attract customer trust by: maintaining social media integration to provide testimonials as recommendations for products or services provided by PT XYZ and developing new service features to provide money guarantees return. Providing convenience in exchanging vouchers by using smartphone technology to exchange vouchers without carrying printed voucher paper. (2) Maintaining or improving services to provide shopping enjoyment at PT XYZ Daily Deals such as maintaining customer service by providing training on performance and service and being selective in choosing merchants which has good quality offerings. What companies must prepare to be able to retain customers and retain traders is to focus more on marketing and increasing brand awareness. In addition, because technological innovation is developing very rapidly, companies must also look at threats and opportunities from the external environment that are tailored to consumer needs. So that consumers' desires and expectations can be well received.